Pengaruh terapi psikoreligius (dzikir) dan progresive muscle relaxation dengan pendekatan caring terhadap kecemasan pada pasien tindakan kemoterapi - Danang Tri Yudono; Shanti Wardaningsih; Novita Kurniasari (STIKes Surya Global Yogyakarta, 2019)
Breast cancer patients who undergo chemotherapy often experience psychologic disorders in the form of anxiety. One of the efforts of medical treatment for cancer treatment is chemotherapy. Chemotherapy action resulted in physical and psychological side effects, one of the psychological effects that arise that is anxiety. Generally, management of anxiety can be pharmacological and non-pharmacological, one of the non-pharmacological management of Progresife Muscle Relaxation and dhikr therapy. The purpose of this study is to analyze the effect of therapy (dzhikr) and Progressive Muscle Relaxation therapy with caring approach to the anxiety level of patients Breast cancer with chemomotherapy. This research used Quasi Experiment design with pretest and posttes with control design, with total sample 44 which is divided into control and intervention group, sampling technique used purposive sampling according to inclusion and exclusion criteria. Instruments research used Zung Self Anxiety Rating Scale (ZSAS) questioner and checklist dzhikr and PMR. Analysis of research data used paried t-test and indenpenden t-test samples. The results showed that there was influence of therapy zhikr and Progressive Muscle Relaxation with caring approach to the anxiety level of ca mamae patients with chemomotherapy with p value=0,007(p value 0,05). Conclusion research there was influence of therapy zhikr and Progressive Muscle Relaxation with caring approach to the anxiety level of ca mamae patients with chemomotherapy.